Employee Development Analysis In Increasing Work Productivity at PT. Bank BTPN Sungguminasa Branch, Gowa Regency - Muh Nur Rasyid; Anur achsanuddin UA; Muhammad Yusuf (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study was to determine the effect of employee development on work productivity at PT. Bank BTPN Sungguminasa Branch, Gowa Regency. Employee development is one of several factors that can affect the level of work productivity. Development is an additional basic salary that is not expected by employees, but only part of it can be given only having certain achievements or certain skills and do not bother when asked to complete as soon as possible, such as reports or receipts that must be reported. This research was conducted using a simple linear regression analysis tool, R2 test and t test to analyze the close relationship of 1 variable, and the results of the discussion that the value of the variable regression coefficient (X) or employee development is 0.458 so it can be said that the employee development variable (X) positive effect on work productivity by 45.8%. From the results of the regression analysis, the t-count value was 3.524 t-table was 2.042 and the significance value (sig.) was 0.001 0.05. So it can be concluded that Ho is rejected and Ha is accepted, which means that employee development (X) has a significant effect on work productivity